Future elementary school teachers’ research culture formation employing individual assignments - Dauren Buribayev; Gulshat Bakhtiyarova; Assan Tuxanbayev (Qubahan Academic Journal)
In the modern dynamic society, quality education and the development of children’s creative abilities are the merits of successful teachers. The modern teacher must have independent learning skills, high motivation and developed research culture skills for effective teaching. The research aims to test the impact of individual student activity – future elementary school teachers, on the development of their research culture. The study was conducted employing various methods, using questionnaires to study the ability of future elementary school teachers to apply creative approaches and conduct pedagogical research in practice. The research participants were 32 teachers with more than 5 years of experience, a PhD degree, and 348 students – future elementary school teachers. Studied the level of motivation as a predictor of the research culture of students adapted and conducted a survey on the questionnaire of creative teaching, as well as self-assessment of students in solving research problems. Before the experiment, most students had low levels of motivation to learn online and self-study, as well as the results of creative teaching in the future, self-evaluation of the possibility of solving research. The introduction of the experimental factor in the learning process – students’ performance of independent assignments for three academic semesters, built on a gradual introduction to research activities, expansion and affirmation of knowledge about the need to find scientific ways to build lessons and learning process in general, the features and process of pedagogical research, had a positive impact on student’s motivation to learn, self-assessment of task capability and creative teaching ability in the bud The final ResCul survey shows students’ knowledge of research culture sufficiently formed. The results obtained apply to students who are studying in the speciality “Pedagogy and Methodology of Elementary Education”.